2017
DOI: 10.1016/j.jfda.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Time course effects of fermentation on fatty acid and volatile compound profiles of Cheonggukjang using new soybean cultivars

Abstract: In this study, we investigated the effects of the potential probiotic Bacillus subtilis CSY191 on the fatty acid profiles of Cheonggukjang, a fermented soybean paste, prepared using new Korean brown soybean cultivars, protein-rich cultivar (Saedanbaek), and oil-rich cultivar (Neulchan). Twelve fatty acids were identified in the sample set-myristic, palmitic, palmitoleic, stearic, oleic, vaccenic, linoleic, α-linolenic, arachidic, gondoic, behenic, and lignoceric acids-yet, no specific changes driven by ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…+, Detected; -Not detected. These results originated from previous research [24][25][26][27][28]. CFU, colony forming unit.…”
Section: Characteristics Of Bacillus Species Isolated From Chungkookjangmentioning
confidence: 80%
See 1 more Smart Citation
“…+, Detected; -Not detected. These results originated from previous research [24][25][26][27][28]. CFU, colony forming unit.…”
Section: Characteristics Of Bacillus Species Isolated From Chungkookjangmentioning
confidence: 80%
“…The type of Bacillus in chungkookjang influences the flavor of chungkookjang, mostly by modulating the fatty acids produced during fermentation [25] that play a crucial role in the flavor and aroma, which determine consumer acceptance. Chungkookjang made with B. amyloliquefaciens has a less unacceptable odor and greater consumer acceptance (Table 1) [24,26,27].…”
Section: Characteristics Of Bacillus Species Isolated From Chungkookjangmentioning
confidence: 99%
“…CKJ prepared using 7% B. subtilis contained the highest value of oleic acid (14.79 ± 0.33) and lowest value of linoleic acid (60.60 ± 1.01). Recently, Cho et al (2017) reported that Neulchan, soybean cultivars showed palmitic acid (10.33 ± 0.44) and stearic acid (3.61 ± 0.15) after 48 h of fermentation using B. subtilis CSY19. This change is occurred due to the variation in cultivars.…”
Section: Changes In Metabolites Of Ckjmentioning
confidence: 99%
“…Compositions and contents of volatile compounds in fermented soybean products has steadily studied and, in particular, butanoic acid, 3-methylbutanoic acid, 2-pentylfuran, 2-and 3-methylbutanal, methyl 2-methylbutanoate, 4-methylpentanoate, and some pyrazines were regarded as main volatile compounds having unique flavor characteristics in fermented soybean pastes (Cho et al, 2017;Yoo et al, 1999). On the other hand, some volatile compounds, such as 2-and 3-methylbutanal, phenylacetaldehyde, furfural, hexanal, 2,5-dimethyl-4-hydroxy-3-(2H)-furanone, 2,4-decadienal, and phenol compounds, were reported as main volatile compounds in various buckwheat-based products (Starowicz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%